Climate variation in the Thar Desert since the Last Glacial Maximum and evaluation of the Indian Monsoon - Roy, Priyadarsi D.; Singhvi, Ashok K. (TIP Revista Especializada en Ciencias Químico-Biológicas, 2016)
Thar Desert is a rainfall deficient (~500-100 mm/year) region in the northwestern India. Previously published information on sediment facies, mineralogy, and radiocarbon chronology helped to reconstruct orbital-scale lake stands and variations in water column salinity of five different lacustrine basins in the desert. We evaluated the hydrological conditions with respect to strength (i.e., amount and geographic coverage) of the southwest summer monsoon since the last glacial maximum (LGM). Between LGM and c.15 cal. ka BP, the eastern basins hosted saline and hypersaline playa lakes and the western part had an intermittent variable lake. A shift from saline-hypersaline playa lakes to perennial deep lakes occurred in the eastern margin at c.15 cal. ka BP as more summer insolation increased sea surface temperature (SST) of the Indian Ocean and strengthened the southwest summer monsoon. During the Pleistocene-Holocene transition, the highest summer insolation as well as warmer SST of the Indian Ocean increased the amount of summer precipitation and expanded the southwest monsoon over the entire desert. However, more winter precipitation and minimal summer rainfall maintained perennial lakes across the desert during the early and middle Holocene. Over the middle-late Holocene, the regional arid conditions were contemporary to intervals of reduced summer insolation, southerly located Inter-Tropical Convergence Zone and frequent El-Niño Southern Oscillation.